The Resource Curse in the Gulf Region: Charting a Path for Long-term Economic Sustainability - Ateba, Benedict Belobo; Enwereji, Prince Chuwuneme (International Journal of Energy Economics and Policy, 2024)
The economies of the Gulf States have been reliant on abundant petroleum resources for over a century. The region has experienced substantial economic success in recent decades, attributed to its competitive advantage as the world’s oil empire. This success is especially noteworthy given that oil is a major economic resource in the area. However, a new debate has emerged, focusing on the concept of the resource curse resulting from the overdependence of Gulf economies on the petrol dollar. This reliance jeopardizes the long-term and future economic sustainability of the Gulf Cooperation Council (GCC) states. This piece employs a narrative literature review to illustrate how petroleum has shaped the economic landscape, and also the oil market volatility on the economic landscape of the region. The review emphasizes on the necessity for the region to shift its economic and institutional over-dependence away from the petrol dollar to other sustainable alternative economic domains. The review proposes strategic economic directions to guide the region towards a diversified and sustainable economic portfolio, reflecting significant potential for the economy of the region and its states. Sustainable economic development portfolios such as sustainable agriculture, renewable energy, smart cities, real estate development, sports, banking, tourism, and travel were analyzed.